Analisis Konflik India-Pakistan di Kashmir dari Perspektif Hukum Internasional: Analisis atas Hak Penentuan Nasib Sendiri dan Kedaulatan Teritorial - Karo, Erland Zuhdi Karo; Prakosa, Reza Bintang (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The India-Pakistan conflict over Kashmir, which has peaked again in 2025, is a reflection of historical tensions that have been ongoing since 1947, with issues of self-determination and territorial sovereignty at its core. This research analyzes recent conflict dynamics, including unilateral Indian actions such as the revocation of Jammu and Kashmir's autonomous status, the suspension of the Indus Waters Treaty, and the escalation of military operations into civilian areas, which significantly increase the risk of humanitarian law and human rights violations. In addition, the involvement of non-state armed groups allegedly supported by Pakistan raises serious questions about state responsibility under international law, particularly the doctrine of effective control. This study also highlights the role of third parties such as the United States, China, the United Kingdom and Saudi Arabia that emphasize the global geopolitical dimension of the conflict, and assesses the effectiveness of dispute resolution mechanisms that have been more tactical than substantive. Using a normative juridical and descriptive qualitative approach, this study emphasizes the need to reform international dispute resolution mechanisms and strengthen state accountability within the framework of international law in order to create a comprehensive and sustainable solution to the Kashmir conflict.